The Influence of a Networked Environment on the Professional Changes - Umlauf, Konrad (Knygotyra, 2002)
The article discusses the requirements for the staff of a public library formed by the Internet, management reform, emergence of knowledge society and budget crisis since the ninth decade. The main focus is on the requirements for work in a networked environment: new management, professional development, social and public performance, professional methodical competence and skills. The article is concluded by the discussion how these changes influence the training and continuing education of library staff. The conclusion is made that the staff of a public library is partly competent to perform job in the networked environment, finds many possibilities to acquire necessary competence and has developed self-consciousness and understanding of the adoption of new requirements. However, the professional development system is inadequate and continuing education mainly relies on the personai initiative and activity of a librarian.
Keywords: -